PERAN PENDIDIKAN DALAM MEMBANGUN KETAHANAN BUDAYA DI ERA GLOBALISASI - Diva Nadiah, Abdul Khobir, Salsabila Febri Urianti, Askia Ramadhani Ishaq, Eka safitri (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The era of globalization has brought increasingly intense flows of information, technology, and cross-cultural interaction, posing challenges to the sustainability of national identity and cultural resilience. Education plays a strategic role in strengthening cultural resilience through the internalization of values, the preservation of traditions, and the reinforcement of students’ character and cultural literacy. This study aims to analyze the role of education in enhancing cultural resilience amid rapid global change. The method employed is a literature review by examining various scholarly sources related to education, globalization, and culture. The findings indicate that education functions as an agent of cultural value transmission, a means of fostering critical awareness toward foreign cultures, and a medium of innovation to adapt and revitalize local culture. Furthermore, the integration of culture-based curricula, the application of contextual learning approaches, and the strengthening of a culturally grounded school ecosystem have proven effective in building students’ cultural resilience. Therefore, education makes a significant contribution to sustaining national culture while equipping younger generations to compete globally without losing their cultural identity.